2016
DOI: 10.1017/s0007114516002774
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between obesity in pets and children: the addiction model

Abstract: Obesity in pets is a frustrating, major health problem. Obesity in human children is similar. Prevailing theories accounting for the rising obesity rates – for example, poor nutrition and sedentary activity – are being challenged. Obesity interventions in both pets and children have produced modest short-term but poor long-term results. New strategies are needed. A novel theory posits that obesity in pets and children is due to ‘treats’ and excessive meal amounts given by the ‘pet–parent’ and child–parent to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…It has been suggested that styles of pet ownership might mirror parenting styles and provide comparative insights into the links to childhood obesity [131]. Behavioural addiction treatment methods are recommended for both overweight children and overweight pets, and studies of outcomes of these approaches are likely to be of value to both disciplines [132].…”
Section: One Health Approach To Obesity and Diabetesmentioning
confidence: 99%
“…It has been suggested that styles of pet ownership might mirror parenting styles and provide comparative insights into the links to childhood obesity [131]. Behavioural addiction treatment methods are recommended for both overweight children and overweight pets, and studies of outcomes of these approaches are likely to be of value to both disciplines [132].…”
Section: One Health Approach To Obesity and Diabetesmentioning
confidence: 99%
“…There are obvious similarities between children and pets, as both have their lifestyle and diet determined by a parent or owner. Although some have suggested an 'addiction model' of obesity in both children and pets (Pretlow and Corbee, 2016), others have suggested associations with different parenting and ownership styles (German, 2015). Both an 'authoritarian' style, where there is too much parental control, and an 'indulgent' style, where control is too lax, are associated with obesity in children.…”
Section: The Psychology Of Weight Lossmentioning
confidence: 99%
“…Horses no doubt do the same. A number of strategies used to cope with feed restriction in children (Pretlow and Corbee, 2016) might be applied to horses. The horse should not be exposed to trigger factors for eating, such as stress, boredom, the sight of food or other stimuli associated with feeding.…”
Section: The Psychology Of Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Predisposing factors for feline obesity are summarised in Table 2 . Recently, Pretlow and Corbee [ 96 ] described resemblances between childhood and pet obesity as both pet-parents and child-parents try to obtain affection by giving treats and/or large meals. Dietary factors include highly palatable, high-energy diets, unrestricted access to food [ 97 , 98 , 99 ], and inclusion of homemade food, table scraps and/or treats [ 98 ].…”
Section: Energy Efficiency Weight Gain and Obesitymentioning
confidence: 99%